2014
DOI: 10.1002/cncr.28524
|View full text |Cite
|
Sign up to set email alerts
|

Severe infections in children with acute leukemia undergoing intensive chemotherapy can successfully be prevented by ciprofloxacin, voriconazole, or micafungin prophylaxis

Abstract: BACKGROUND The purpose of the current study was to prevent bloodstream infection and invasive fungal infection (IFI) by administering prophylactic antibiotic and antifungal agents during intensive chemotherapy in patients being treated for acute leukemia. METHODS Prophylaxis treatment was administered during intensive chemotherapy in children with acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) from January 1, 2010 to December 31, 2012. Oral ciprofloxacin (at a dose of 300 mg/m2/12 hours) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 21 publications
(39 reference statements)
2
81
0
5
Order By: Relevance
“…A retrospective study from St. Jude Children's Research Hospital (SJCRH) in patients with AML found that the use of intravenous cefepime or vancomycin in conjunction with oral ciprofloxacin or a cephalosporin significantly reduced the incidence of bacterial infection and sepsis compared with patients receiving only oral or no antibiotic prophylaxis [112]. Another retrospective study reported a significant reduction in Gram positive, sterilesite infections with antibiotic prophylaxis [113]. While it is suggested that antibiotic prophylaxis is beneficial, prospective randomized trials are required in pediatric patients with AML.…”
Section: Supportive Treatmentmentioning
confidence: 99%
“…A retrospective study from St. Jude Children's Research Hospital (SJCRH) in patients with AML found that the use of intravenous cefepime or vancomycin in conjunction with oral ciprofloxacin or a cephalosporin significantly reduced the incidence of bacterial infection and sepsis compared with patients receiving only oral or no antibiotic prophylaxis [112]. Another retrospective study reported a significant reduction in Gram positive, sterilesite infections with antibiotic prophylaxis [113]. While it is suggested that antibiotic prophylaxis is beneficial, prospective randomized trials are required in pediatric patients with AML.…”
Section: Supportive Treatmentmentioning
confidence: 99%
“…Нейробластома 33 (20,4) Острый миелобластный лейкоз 29 (18) Острый лимфобластный лейкоз 20 (12,4) Ювенильный миеломоноцитарный лейкоз 11 (6,6) Первичный иммунодефицит В контексте данного исследования все пациенты получали препарат Вифенд (вориконазол) в качестве профилактики грибковой инфекции в средней дозе 9 мг/кг/сут в 2 приема каждые 12 ч с последующей под-держивающей дозой 8 мг/кг 2 раза в сутки. Важно от-метить, что в период с 2012 по 2013 г. препарат вводился внутривенно и в качестве таблетированных препара-тов, а начиная с 2014 г. появилась опция использования суспензии, что в ряде случаев (мукозит, малый возраст пациентов) позволило добиться лучшей приверженно-сти терапии.…”
Section: нозологические единицы число пациентов (%)unclassified
“…Было показано, что вориконазол был эффективным и безопасным прежде всего для первичной и вторич-ной профилактики грибковых инфекций у детей при ТГСК и химиотерапии [17,18]. Эффективность данного препарата, по разным данным, составляет от 48 до 84 % [19,20].…”
unclassified
“…The use of Dasatinib or imatinib in Ph (+) ALL may improve outcome. Prophylaxis with antibacterial and antifungal agents to patients with profound neutropenia in the early phase of therapy can decrease severe infections [12]. Overall, 6-7% of ALL patients need SCT, including those who relapses early.…”
Section: Treatmentmentioning
confidence: 99%